3D-extrusion printing of stable constructs composed of photoresponsive polypeptide hydrogels. Issue 34 (6th August 2019) - Murphy, Robert D.; Kimmins, Scott; Hibbitts, Alan J.; Heise, Andreas
Abstract : Printing of novel linear polypeptide hydrogel bioinks and stabilisation of structures by post-printing UV-triggered crosslinking through catalyst free thiol–yne click chemistry of cysteine and propiolated 4-arm PEG. Abstract : The development of printable hydrogels with functional responsive crosslinking is vital to new age 3D printing materials in biomedical science. Disclosed here is a 3D printable UV responsive crosslinking system based on polypeptides incorporating glutamic acid, isoleucine and nitrobenzyl (NB) protected cysteine groups in a random and block copolymer. The hydrogel ink, encompassing the copolypeptide hydrogel carrier and 4-arm PEG-propiolate, can be readily extruded to produce mechanically stable constructs consisting of a number of geometries due to their remarkable shear-thinning ability. Exploiting the use of a catalyst free thiol–yne click chemistry between the cysteine residues and the propiolate groups upon UV curing, crosslinked hydrogel constructs with greater than 10 layers are fully stabilised and show improved stiffness which allow for them to be easily manipulated. This work can potentially offer a new crosslinking tool to explore in the field of 3D printing, providing highly stable hydrogel structures.